PEMBERIAN TOTAL FENOL TERIPANG PASIR (Holothuria scabra) UNTUK MENINGKATKAN LEUKOSIT DAN DIFERENSIAL LEUKOSIT IKAN MAS (Cyprinus carpio) YANG DIINFEKSI BAKTERI Aeromonas Hydrophila - Achmad Suhermanto; Sri Andayani; M Maftuch (Jurnal Kelautan, 2011)
Freshwater fishery commodities are most likely to be increased production of carp (Cyprinus carpio). Intensification of cultivation which raises new problems with fish disease outbreaks caused by Aeromonas hydrophila. Providing of immunostimulatory bioactive compounds of sea cucumbers (Holothuria scabra) can enhance non-specific immune responses in the goldfish as a mechanism of defense against disease. The purpose of this study is to determine the role and optimal dose of total phenols sea cucumber in enhancing non-specific immune response seen from the hematology parameters Extraction of bioactive components from sea cucumber prepared by using methanol and fractionated with ethyl acetate solvent (v/v). Identification of total phenols in ethyl acetate fraction performed using UV-Vis spectrophotometer and infrared. Total phenol produced was tested on carp with intraperitonial injection, the concentration of 0.09, 0.18 and 0.27 mg phenol/kg fish. Challenge test was done by using the Aeromonas hydrophila (107 cells/ml) through the immersion method. The observations included hematological parameters and total plasma proteins.The observations of hematological parameters that Leukocytes, Neutrophils pre-and post-infection were significantly increased. Lymphocyte pre infection was increased significantly and post-bacterial infection was decreased significantly. Eosinophils, Monocytes pre-and post-bacterial infection were not differ significantly between treatment. The use of phenolic compounds at 0.09 mg / kg can be increase of non-specific immune response in carp (Cyprinus carpio). Key Words : Total phenol, Aeromonas hydrophila, Cyprinus carpio, nonspecific immune response